2014
DOI: 10.1111/bjh.12918
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood cells chimerism after unrelated cord blood transplantation in children: kinetics, predictive factors and impact on post‐transplant outcome

Abstract: SummaryThis study aimed to describe kinetics of complete donor chimerism occurrence (cDC, >99Á9% donor) after unrelated cord blood transplantation (UCBT), to identify its predictive factors and its impact on post-transplant outcome. Ninety-four children who received single UCBT after a myeloablative conditioning regimen had blood chimerism evaluation at predefined post-transplant dates, using a real-time polymerase chain reaction method with 0Á1% sensitivity. Cumulative incidence of cDC at 1 year post-transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…Significant recipient chimerism is associated with a higher frequency of donor tolerance [9, 10] and could affect the interpretation of chronic GVHD biomarkers when donor-derived hematopoiesis is not fully engrafted. In patients with questionable engraftment, chimerism should be examined, and the patient should be excluded from biomarker studies if results show < 90% donor chimerism, ideally in either lymphoid or myeloid populations.…”
Section: Risk Factors and Covariates To Considermentioning
confidence: 99%
“…Significant recipient chimerism is associated with a higher frequency of donor tolerance [9, 10] and could affect the interpretation of chronic GVHD biomarkers when donor-derived hematopoiesis is not fully engrafted. In patients with questionable engraftment, chimerism should be examined, and the patient should be excluded from biomarker studies if results show < 90% donor chimerism, ideally in either lymphoid or myeloid populations.…”
Section: Risk Factors and Covariates To Considermentioning
confidence: 99%
“…Consensus is still missing on the best cut-off value for positivity in qPCR as well as the preferable use of bone marrow (BM) or peripheral blood (PB), the latter with obvious logistical advantages for sample acquisition at sufficiently high abundance but with potentially lower informative value compared with BM, the natural environment for relapse onset. Moreover, only a single report has to our knowledge so far addressed the question of engraftment monitoring by qPCR, in the particular setting of umbilical cord blood SCT [44]. Possibly because of the still limited available evidence for its clinical utility, most clinical laboratories still do not use qPCR for routine chimerism testing but prefer STR as the standard method.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies found that the incidences of cGVHD after CBT were 11.6% and 18.0%. 24,25 In our study, cGVHD occurred in 5 of the 21 CBT patients (24%).…”
Section: Discussionmentioning
confidence: 46%